2014
DOI: 10.1158/0008-5472.can-13-2042
|View full text |Cite
|
Sign up to set email alerts
|

The Alarmin HMGN1 Contributes to Antitumor Immunity and Is a Potent Immunoadjuvant

Abstract: Alarmins are endogenous mediators that are elicited rapidly in response to danger signals, enhancing innate and adaptive immune responses by promoting the recruitment and maturation of antigen-presenting cells (APC). The nucleosome-binding protein HMGN1 is a potent alarmin that binds TLR4 and induces antigen-specific Th1 immune responses, but its contributions to antitumor immunity have not been explored. We found that ovalbumin (OVA)-expressing EG7 mouse thymoma cells grew much faster in Hmgn1-deficient mice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 46 publications
(82 reference statements)
1
77
0
Order By: Relevance
“…HMGN1‐stimulated protective anti‐tumor immunity relied on T cells because it was abolished by depletion of CD4 + and CD8 + T cells. Mice DNA vaccinated with a construct directing the expression of HMGN1‐gp100 fusion protein indeed induced gp100‐specific immune responses and resistant to challenge with mouse B16 melanoma, providing additional support for the crucial role of HMGN1 in the generation of anti‐tumor immunity …”
Section: Alarmins and Tumor Immunitymentioning
confidence: 83%
See 1 more Smart Citation
“…HMGN1‐stimulated protective anti‐tumor immunity relied on T cells because it was abolished by depletion of CD4 + and CD8 + T cells. Mice DNA vaccinated with a construct directing the expression of HMGN1‐gp100 fusion protein indeed induced gp100‐specific immune responses and resistant to challenge with mouse B16 melanoma, providing additional support for the crucial role of HMGN1 in the generation of anti‐tumor immunity …”
Section: Alarmins and Tumor Immunitymentioning
confidence: 83%
“…HMGN1 preferentially induces Th1‐polarized immune responses and has recently been shown to promote the development of protective anti‐tumor immunity . EG7 mouse thymoma expressing OVA as a surrogate tumor‐associated antigen (TAA) was found to grow much faster in HMGN1‐deficient mice than littermate‐matched controls . In addition, HMGN1 −/− mice exhibited a higher incidence of spontaneous formation of multiple malignant tumors than their HMGN1 +/+ littermates .…”
Section: Alarmins and Tumor Immunitymentioning
confidence: 99%
“…Secreted outside cells, HMGN1 is involved in inflammatory processes. Extracellular HMGN1 promotes antigen-specific immune responses by promoting the activation and recruitment of antigen-presenting cells (APCs) through toll-like receptor 4 (TLR4) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…4). Plasmid DNA constructs were designed as described previously [28]. Briefly, the fusion gene for HMGN1-gp100 was cloned into the eukaryotic expression plasmid pcDNA 3.1/mycHis B (Life Technologies, Carlsbad, CA).…”
Section: Immunization Of Micementioning
confidence: 99%
“…As a result, the HMGN1-gp100 fusion may stimulate an immune response against tumors that express this antigen. Research in the Oppenheim lab has shown that this HMGN1-gp100 DNA vector can amplify cellular immune responses that protect mice against melanoma tumor challenge as compared to separate HMGN1 and gp100 DNA vectors [28]. Herein, we study the immunostimulatory potential of this plasmid encapsulated in self-assembled peptide gels.…”
Section: Introductionmentioning
confidence: 99%